ANALISIS KESESUAIAN BUKU TEKS MATEMATIKA KELAS VII DENGAN KOMPETENSI INTI DAN KOMPETENSI DASAR KURIKULUM 2013 - Sanianajiba Nugroho Putri (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2021)
This study aims to describe the level of conformity between Class VII Mathematics Textbooks with Core Competencies and Basic Competencies of Curriculum 2013. Starting from the suitability of Basic Competencies from Core Competencies 1, Core Competencies 2, Core Competencies 3, and Core Competencies 4. The research method used is qualitative descriptive approach The primary data source used is the Mathematics Textbook for Class VII Semester 2 Revised 2017 Edition published by the Ministry of Education and Culture. While the secondary data sources are journals and relevant previous research results. The data collection used is a document content analysis (content analysis). To check the validity of this research data by increasing persistence. This descriptive research is intended to describe and analyze the level of conformity of the book with the Core Competencies and Basic Competencies. The results of this study, the level of conformity of the Mathematics Textbook for Class VII Semester 2 Revised 2017 Edition with the Implementation of Core Competencies and Basic Competencies of the 2013 Curriculum obtained a score of 86.5% in the